Preparation method of ceramic tile with improved glaze antifouling performance and application thereof
Patent Information
- Application Number
- CN202611286375.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-23
AI Technical Summary
[0003]针对上述缺陷,本发明的目的在于提出一种提升釉面防污性能的陶瓷砖的制备方法,解决现有的陶瓷砖釉面无法在保持釉面光泽度的前提下达到防污等级4级的问题
1.通过引入活性氧化铝微粉替代α-Al2O3粉体,结合上述烧成方法,使釉料烧结后形成致密釉面,防污等级显著提升。活性氧化铝在1190℃时处于γ→α相变的前期,表面活性最高,能与熔融玻璃相中Ca²+、Mg²+快速反应生成纳米级铝酸盐晶核。若温度偏低(<1188℃),液相量不足,反应不充分;若温度偏高(>1192℃)或保温过长,活性氧化铝转化为粗大α-Al2O3颗粒,失去反应活性,仅起机械填充作用,无法形成化学键合的防污致密层。因此,1190±1℃的精确控制是实现防污等级跃升的必要条件。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic tile protective glaze technology, and in particular to a method for preparing ceramic tiles that improves the anti-fouling performance of the glaze surface and its application. Background Technology
[0002] Existing protective glazes for ceramic tiles suffer from unstable stain resistance during long-term use. While conventional alumina as a glaze component can improve wear resistance, it offers limited improvement in glaze density and stain resistance, typically achieving a stain resistance level of only around 3 after fine polishing. Finding a stable way to improve the stain resistance level to 4 or higher without sacrificing glaze gloss and transparency is a pressing issue for the industry. Summary of the Invention
[0003] To address the aforementioned shortcomings, the present invention aims to propose a method for preparing ceramic tiles that improves the anti-fouling performance of the glaze, thereby solving the problem that existing ceramic tile glazes cannot achieve a level 4 anti-fouling rating while maintaining the gloss of the glaze.
[0004] To achieve this objective, the present invention adopts the following technical solution: A method for preparing ceramic tiles with improved anti-fouling properties of glaze, wherein the protective glaze layer is fired from a protective glaze material, the raw materials of which include: potassium feldspar, sodium feldspar, quartz powder, calcite, dolomite, calcined talc, zinc oxide, barium carbonate, zircon sand powder, and materials containing active alumina; wherein the active alumina is alumina with γ-Al2O3, δ-Al2O3, or θ-Al2O3 as the main crystalline phase, and the content of active alumina is 1.8~2.5% (mass ratio) of the glaze raw materials. The firing time for the protective glaze is 46-69 minutes, with the highest surface temperature of the fired brick blank being 1190±1℃ and the holding time at the highest temperature being 7.5±0.5 minutes.
[0005] Preferably, the material containing active alumina is calcined bauxite powder calcined at 650~850℃.
[0006] Preferably, the raw materials for the glaze, by weight, include: Potassium feldspar 28-35 parts, 12-18 parts of albite, 15-22 parts quartz powder 8-12 parts of calcite 1-3 parts dolomite Calcined talc (1-3 parts) 1-3 parts zinc oxide Barium carbonate 0.5-1.5 parts, 2-5 parts zircon sand powder 10-14 parts of calcined bauxite powder.
[0007] Preferably, the glaze is prepared by wet ball milling, in which the raw materials of the glaze, water and dispersant are added together to a ball mill and ground and mixed until the fineness D90≤10μm and the specific gravity of the glaze slurry is 1.75-1.85g / cm³, thus obtaining the glaze slurry.
[0008] Preferably, a combination of bell-shaped glazing and spray glazing is used, with a glazing amount of 400-600g / m².
[0009] Preferably, the firing temperature is set with control points M21, M31, M45, M53 and M57, and the temperatures at each control point are as follows: brick surface temperature: M21: 918±10℃, M31: 1020±10℃, M45: 1105±10℃, M53: 1175±10℃, M57: 1190±1℃; brick bottom temperature: M021: 864±10℃, M027: 1030±10℃, M043: 1111±10℃, M055: 1180±10℃, M057: 1193±1℃. The heating time for each zone is as follows: 20-28 min for kiln entry → M21, 7-11 min for M21 → M31, 9-14 min for M31 → M45, 7-10 min for M45 → M53, and 3-6 min for M53 → M57. After passing through the M57 control point, maintain the temperature for 7-8 minutes; then cool to 850±10℃ for 3-5 minutes, then cool to 550±10℃ for 8-12 minutes, and finally allow to cool naturally.
[0010] A ceramic tile prepared by the above-mentioned preparation method, having a glaze anti-fouling level ≥4 and a glaze gloss ≥94°.
[0011] The main equipment of the roller kiln in this scheme is a natural gas open-flame wide-body roller kiln as the firing equipment. A roller kiln is a continuous industrial kiln that uses rotating rollers to transport materials, sequentially completing processes such as preheating, sintering, and cooling. It is widely used in the firing of ceramic wall and floor tiles and daily-use ceramics. Currently, roller kilns commonly employ PID intelligent temperature control technology, with temperature differences ≤ ±1℃ and cross-sectional temperature differences ≤ ±5℃, providing a foundation for precise temperature control. The transmission method is as follows: the brick blanks are placed on ceramic rollers, which are driven to rotate by a motor, allowing the brick blanks to pass through each section of the kiln at a uniform speed.
[0012] This solution utilizes a distributed intelligent temperature control system. In roller kiln temperature control, traditional PID control is ineffective due to the difficulty in establishing an accurate mathematical model of the controlled object. This solution employs a relay feedback-based PID parameter self-tuning method to determine initial PID parameters. Then, using fuzzy control theory, the PID parameters are corrected in real-time based on the absolute value of the deviation and the cumulative absolute value of the deviation during system operation. When parameters or operating conditions change, the PID parameter values are gradually adjusted to ensure the system control performance remains optimal, achieving online intelligent correction of the PID parameters.
[0013] This intelligent control system uses RS-485 serial communication to form a distributed intelligent control system for centralized monitoring of the roller kiln temperature. It has been running continuously in the field for a long time with stable performance, high reliability, and good control performance.
[0014] In addition, to further overcome the large time delay characteristics of the roller kiln system, an adaptive PID control method based on deep reinforcement learning can also be adopted. The PID controller parameters are adaptively adjusted through the TD3 algorithm, and the Smith predictor is used to eliminate the influence of the time delay of the roller kiln system, so that the root mean square error of temperature control is reduced by 5.58~11.42 compared with traditional PID control.
[0015] This solution replaces the outdated relay control system with a PLC and a high-precision temperature control module, integrating over 100 temperature acquisition points. It dynamically adjusts the heating power using a PID self-tuning algorithm to avoid temperature overshoot or lag. By introducing a temperature curve prediction function, it can anticipate temperature fluctuation trends based on historical production data and product firing processes, automatically compensating for heating parameters and improving temperature stability by 40%.
[0016] The technical solution provided by this invention may include the following beneficial effects: 1. By introducing activated alumina micropowder to replace α-Al₂O₃ powder, combined with the above-mentioned firing method, a dense glaze surface is formed after sintering, significantly improving the anti-fouling level. Activated alumina is in the early stage of the γ→α phase transition at 1190℃, exhibiting the highest surface activity, and can react with Ca²⁺ in the molten glass phase. + Mg² + The rapid reaction generates nanoscale aluminate crystal nuclei. If the temperature is too low (<1188℃), the liquid phase is insufficient, and the reaction is incomplete; if the temperature is too high (>1192℃) or the holding time is too long, the activated alumina transforms into coarse α-Al2O3 particles, losing its reactivity and only serving a mechanical filling function, unable to form a chemically bonded, dense antifouling layer. Therefore, precise control of 1190±1℃ is a necessary condition for achieving a significant leap in antifouling level.
[0017] 2. Maximum Temperature Control Accuracy: ±1℃. Precise temperature control ensures that the activated alumina is precisely within the reaction range, avoiding insufficient densification due to underfiring or loss of activity due to overfiring. The maximum temperature of 1190℃ is 10-20℃ higher than the traditional value. This is to ensure sufficient decomposition of calcite and allow the Ca-rich liquid phase to fully react with the activated alumina to form a dense calcium aluminate layer, without being too high and causing overfiring. The high-temperature holding time is precisely controlled at 7.5±0.5min, ensuring that the activated alumina has sufficient time to react with the liquid phase to form a continuous anti-fouling transition layer, without excessive crystallization leading to a loss of transparency. Appropriately extending the firing temperature within the range of 46-69min helps reduce thermal stress microcracks. When the firing temperature is below 1189℃, the glaze melts insufficiently, the liquid phase is insufficient, the activated alumina does not react fully, and the anti-fouling dense layer is incomplete. When the temperature is above 1191℃, the glaze is overfired, the liquid phase is excessive, the glaze surface develops "orange peel" or glaze runs, and the activated alumina dissolves excessively, failing to form an anti-fouling microstructure. When the high-temperature holding time is less than 7.0 min, the liquid phase reaction and filling are insufficient, the pinholes cannot close, and the anti-fouling effect decreases; when it is more than 8.0 min, the grains grow excessively, the glaze gloss decreases, and the body may be over-fired and deformed. When the firing time is less than 60 min, the temperature rises and falls too quickly, the thermal stress is high and cracking is easy, and the glaze is not fully leveled. When the firing time exceeds 75 min, the energy consumption is high and the efficiency is low. Moreover, the prolonged high temperature causes all the active alumina to be converted into α-Al2O3, losing its active advantage.
[0018] 3. Calcined bauxite is obtained by controlling the calcination temperature of bauxite at 650~850℃, which retains some of the transitional alumina formed by the dehydroxylation of boehmite and abundant micropores, achieving a specific surface area ≥80m² / g and a main phase containing γ-Al₂O₃. Calcined bauxite itself contains small amounts of impurities such as SiO₂, TiO₂, and Fe₂O₃, and its main mineral phase is corundum and a small amount of mullite. However, by controlling the calcination temperature, some transitional alumina and a high specific surface area can be retained, providing active alumina. Active Al₂O₃ reacts with alkali metal and alkaline earth metal oxides in the protective glaze at high temperatures to generate fine aluminate crystals or an alumina-rich glass layer, filling the micropores within the glaze and significantly reducing the open porosity of the glaze surface, improving the anti-fouling level from level 3 to level 4 or higher. The high specific surface area and surface hydroxyl groups of the active alumina micropowder can adsorb some alkali metal ions in the glaze slurry during ball milling, serving as preferential nucleation sites during firing and promoting the uniform densification of the glaze layer. Detailed Implementation
[0019] To facilitate understanding of the present invention, a more complete description is provided below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a thorough and complete understanding of the disclosure of the present invention.
[0020] Where specific techniques or conditions are not specified in the examples, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0022] A method for preparing ceramic tiles with improved anti-fouling properties of glaze, wherein the protective glaze layer is fired from a protective glaze material, the raw materials of which include: potassium feldspar, sodium feldspar, quartz powder, calcite, dolomite, calcined talc, zinc oxide, barium carbonate, zircon sand powder, and materials containing active alumina; wherein the active alumina is alumina with γ-Al2O3, δ-Al2O3, or θ-Al2O3 as the main crystalline phase, and the content of active alumina is 1.8~2.5% (mass ratio) of the glaze raw materials. The firing time for the protective glaze is 46-69 minutes, with the highest surface temperature of the fired brick blank being 1190±1℃ and the holding time at the highest temperature being 7.5±0.5 minutes.
[0023] The alumina commonly used in ceramic tile glazes is α-Al₂O₃ powder produced by the Bayer process and calcined at high temperatures. Its main crystalline phase is α-Al₂O₃ corundum, characterized by a stable crystal structure, low surface energy, poor chemical activity, and predominantly regular polygonal particle morphology. In glazes, it primarily functions as a mechanical filler and enhances hardness, but it is unlikely to participate in high-temperature liquid-phase reactions or promote densification. Industrial-grade α-Al₂O₃ typically has a specific surface area ≤5 m² / g and a D50 particle size of 1~5 μm.
[0024] Activated alumina refers to transition-state alumina obtained by controlling the calcination of aluminum hydroxides, such as boehmite and pseudoboehmite. Its main crystalline phases are γ-Al₂O₃, δ-Al₂O₃, or θ-Al₂O₃, exhibiting high specific surface area, abundant surface hydroxyl groups, and numerous lattice defects. During glaze firing, it preferentially reacts with the molten glass phase at the interface, promoting uniform liquid phase distribution and enhancing glaze densification. Industrial-grade activated alumina typically has a specific surface area ≥80 m² / g and a D50 particle size of 0.5~1.5 μm.
[0025] This solution introduces activated alumina micropowder to replace α-Al₂O₃ powder, combined with the aforementioned firing method, resulting in a dense glaze surface after sintering, significantly improving its anti-fouling level. Activated alumina is in the early stage of the γ→α phase transition at 1190℃, exhibiting the highest surface activity, and can react with Ca²⁺ in the molten glass phase. + Mg² + The rapid reaction generates nanoscale aluminate crystal nuclei. If the temperature is too low (<1188℃), the liquid phase is insufficient, and the reaction is incomplete; if the temperature is too high (>1192℃) or the holding time is too long, the activated alumina transforms into coarse α-Al2O3 particles, losing its reactivity and only serving a mechanical filling function, unable to form a chemically bonded, dense antifouling layer. Therefore, precise control of 1190±1℃ is a necessary condition for achieving a significant leap in antifouling level.
[0026] The traditional method for firing protective glazes involves a maximum temperature of 1170~1185℃, with a typical temperature fluctuation of about ±5℃. The high-temperature holding time is 5~8 minutes, which is usually not precisely controlled, and the firing time is 40~60 minutes.
[0027] This design employs a maximum temperature control accuracy of ±1℃ to precisely control the temperature, ensuring that the activated alumina is exactly within the reaction range, avoiding insufficient densification due to under-firing or loss of activity due to over-firing. The maximum temperature of 1190℃ is 10-20℃ higher than the traditional method, aiming to fully decompose calcite and allow the Ca-rich liquid phase to fully react with the activated alumina to form a dense calcium aluminate layer, without exceeding the limits of heat and causing over-firing. The high-temperature holding time is precisely controlled at 7.5±0.5 min to ensure sufficient time for the activated alumina to react with the liquid phase and form a continuous anti-fouling transition layer, without excessive crystallization leading to devitrification. Appropriately extending the firing temperature within the range of 46-69 min helps reduce thermal stress microcracks.
[0028] When the firing temperature is below 1189℃, the glaze melts insufficiently, the liquid phase is insufficient, the activated alumina does not react fully, and the antifouling dense layer is incomplete. When the temperature is above 1191℃, the glaze is overfired, the liquid phase is excessive, and the glaze surface develops an "orange peel" appearance or glaze run-off. Excessive dissolution of activated alumina prevents the formation of antifouling microstructures. When the high-temperature holding time is less than 7.0 min, the liquid phase reaction and filling are insufficient, pinholes cannot close, and antifouling properties decrease. When it is more than 8.0 min, the grains grow excessively, the glaze gloss decreases, and the body may be overfired and deformed. When the firing time is less than 60 min, the temperature rises and falls too quickly, resulting in high thermal stress and easy cracking. The glaze surface is not sufficiently leveled. When the firing time exceeds 75 min, energy consumption is high, efficiency is low, and prolonged high temperature causes all activated alumina to be converted into α-Al2O3, losing its active advantage.
[0029] In the glaze raw materials, potassium feldspar provides K₂O and Al₂O₃, which act as the main flux to reduce the high-temperature viscosity of the glaze, promote the formation of the glassy phase, and improve the gloss of the glaze surface. An appropriate amount of K₂O can reduce the surface tension of the glaze, which is beneficial for the liquid phase to fill pores and reduce the open porosity, thereby improving antifouling performance. The potassium-rich glassy phase formed by the melting of potassium feldspar can wet the surface of activated alumina particles, accelerating the dissolution-crystallization process of activated alumina and forming a uniform and dense transition layer.
[0030] The introduction of sodium feldspar into Na₂O further lowers the initial melting temperature and high-temperature viscosity of the glaze, and forms a mixed alkali effect with potassium feldspar, broadening the melting range. At high temperatures, the low-viscosity liquid phase more easily penetrates into the intermediate layer of the body and glaze, sealing capillaries and reducing the glaze surface staining rate. + Ions can partially enter the spinel defect sites of active alumina, promoting its reactivity.
[0031] Quartz powder provides the SiO2 framework, adjusting the coefficient of thermal expansion of the glaze and improving its hardness and wear resistance. SiO2 is a glass network forger, and the formation of a continuous network structure is the basis for a dense glaze. Activated alumina can capture some of the SiO2 on the surface of quartz particles to form mullite microcrystals or an aluminosilicate transition layer, eliminating microcracks around the quartz particles and reducing stain penetration channels.
[0032] Calcite, when introduced into CaO, decomposes at high temperatures and participates in the formation of the glass network, thus regulating the high-temperature fluidity of the glaze. Appropriate amounts of CaO help reduce high-temperature viscosity and promote the liquid phase filling of pores. Ca² + When reacted with activated alumina, it can generate calcium aluminate (such as CaAl2O4, CaAl4O7) microcrystals, which can "stitch" microcracks and seal capillaries, thus enhancing the antifouling effect.
[0033] Dolomite simultaneously introduces CaO and MgO, further regulating the high-temperature viscosity and surface tension of the glaze. MgO can form magnesium aluminum spinel (MgAl2O4) microcrystals with activated alumina. This spinel phase is extremely stable, preventing the propagation of microcracks on the glaze surface.
[0034] Burning talc provides MgO and SiO2, reducing the coefficient of thermal expansion and improving the thermal stability and crack resistance of the glaze. Improved thermal stability prevents microcracks from forming during firing and cooling, avoiding the formation of new channels for stain penetration.
[0035] Zinc oxide is a strong flux, improving the gloss of the glaze and enhancing its chemical stability. It also improves the glaze's resistance to acid and alkali corrosion, preventing everyday cleaning agents from damaging the dense glaze layer. Zn² + It can enter the aluminosilicate glass network, enhancing network connectivity and reducing the number of stain adsorption points.
[0036] The introduction of barium carbonate into BaO improves the refractive index and gloss of the glaze, while also having a fluxing effect. Ba² +With a large ionic radius, it can fill the gaps in the glass network, further densifying it.
[0037] The introduction of zircon sand powder into ZrO2 and SiO2 significantly improves the wear resistance and chemical stability of the glaze. Zircon sand particles form a dispersed reinforcing phase within the glaze, enhancing its scratch resistance and preventing scratches from becoming hidden stains. The slow dissolution of zircon sand at high temperatures provides heterogeneous nucleation sites for activated alumina, promoting uniform crystallization.
[0038] Preferably, the material containing active alumina is calcined bauxite powder calcined at 650~850℃.
[0039] Calcined bauxite is obtained by controlling the calcination temperature of bauxite at 650~850℃, so that it retains some of the transitional alumina formed by the dehydroxylation of boehmite and abundant micropores, achieving the standard of specific surface area ≥80m² / g and main phase containing γ-Al2O3.
[0040] Calcined bauxite itself contains small amounts of impurities such as SiO2, TiO2, and Fe2O3. Its main mineral phases are corundum and a small amount of mullite. However, by controlling the calcination temperature, some transition-state alumina and a high specific surface area can be retained, providing active alumina. Active Al2O3 reacts with alkali metal and alkaline earth metal oxides in the protective glaze at high temperatures to generate fine aluminate crystals or an alumina-rich glass layer, filling the micropores within the glaze and significantly reducing the porosity of the glaze surface, improving the anti-fouling level from level 3 to level 4 or higher. The high specific surface area and surface hydroxyl groups of the active alumina micropowder can adsorb some alkali metal ions in the glaze slurry during ball milling, serving as preferential nucleation sites during firing and promoting the uniform densification of the glaze layer.
[0041] Preferably, the raw materials for the glaze, by weight, include: Potassium feldspar 28-35 parts, 12-18 parts of albite, 15-22 parts quartz powder 8-12 parts of calcite 1-3 parts dolomite Calcined talc (1-3 parts) 1-3 parts zinc oxide Barium carbonate 0.5-1.5 parts, 2-5 parts zircon sand powder 10-14 parts of calcined bauxite powder.
[0042] This proportion of calcined bauxite powder can provide 1.8~2.5% (by mass) of active alumina. If the amount of calcined bauxite powder added is too small, there are insufficient reactive sites, making it impossible to form a sufficiently dense layer, and the anti-fouling level remains at 3. If the amount added is too large, the glaze's refractoriness increases, but its gloss decreases (potentially below 90°). Excessive aluminate microcrystals cause the glaze surface to become hazy, resulting in poor transparency.
[0043] If too little potassium feldspar is added, the glass phase will not be formed sufficiently, resulting in a decrease in the gloss and density of the glaze and a reduction in its anti-fouling grade; if too much is added, the coefficient of thermal expansion will be too large, making it prone to cracking; the glaze will be too soft and have poor wear resistance.
[0044] If too little albite is added, the initial melting temperature will be too high, the glaze will not spread easily, and the pinholes will increase; if too much is added, the chemical stability of the glaze will decrease, the acid and alkali resistance will deteriorate, and the anti-fouling performance will be unstable.
[0045] If too little quartz powder is added, the glaze will lack hardness and wear resistance, making it prone to scratches and dirt accumulation; if too much is added, the viscosity will increase at high temperatures, making it difficult for the glaze to flow smoothly, and it will easily produce ripples and pinholes, thus reducing the anti-fouling level.
[0046] If too little calcite is added, the fluxing effect will be insufficient, the glaze layer will not be sufficiently densified, and there will be many residual pores; if too much calcite is added, the amount of CO2 decomposition gas will increase, which may lead to pinholes and bubble defects on the glaze surface and reduce the anti-fouling effect.
[0047] If too little dolomite is added, its fluxing and regulating effects are insufficient, resulting in a small contribution to spinel formation; if too much is added, excessive MgO is introduced, causing the glaze to have too low viscosity at high temperatures, making it prone to glaze flow and product deformation.
[0048] Calcined talc is talc powder made by directly calcining talc mud. If too little talc is added, the thermal stability will not be adequately compensated, and micro-cracks may appear. If too little talc is added, the glaze hardness will be too high, and the polishing difficulty will increase. Too much MgO will make the glaze prone to crystallization and opacity.
[0049] If too little zinc oxide is added, the gloss and chemical stability will be insufficient; if too much is added, the firing range of the glaze will be narrowed, and it will be easy to volatilize, which may lead to glaze defects.
[0050] Adding too little barium carbonate has little effect on gloss and density; adding too little results in high cost, while too much BaO will cause the glaze melting temperature range to shift, the glaze surface to become cloudy, and excessive carbonate gas will lead to more pores and poor stain resistance.
[0051] If too little zircon sand powder is added, the wear resistance will be insufficient and the scratch resistance will be poor; if too much is added, the roughness of the glaze surface will increase and the gloss will decrease; if the high-temperature crystallization is excessive, the glaze surface will become rough and the anti-fouling performance will decrease (the grain boundaries become penetration channels).
[0052] Preferably, the glaze is prepared by wet ball milling, in which the raw materials of the glaze, water and dispersant are added together to a ball mill and ground and mixed until the fineness D90≤10μm and the specific gravity of the glaze slurry is 1.75-1.85g / cm³, thus obtaining the glaze slurry.
[0053] Preferably, the ball milling fineness D90 is 8~10μm. When D90>10μm, the number of coarse particles increases, resulting in uneven reaction during firing, pinholes and ripples on the glaze surface, and the anti-fouling grade drops to level 3 or below. When D90<5μm, excessive ball milling consumes energy, increases the viscosity of the glaze slurry, leads to uneven glazing, severe thixotropy of the glaze slurry, and severe shrinkage and cracking after the glaze layer dries. When the specific gravity of the glaze slurry is <1.75, the water content is too high, causing the body to absorb too much water after glazing, reducing the strength of the brick body, and resulting in an insufficient anti-fouling layer due to an excessively thin glaze layer. When the specific gravity is >1.85, the glaze slurry has poor fluidity, making it difficult to control the glaze thickness evenly, and easily causing glaze shrinkage in thick glaze areas and exposure of the base layer in thin glaze areas.
[0054] Preferably, a combination of bell-shaped glazing and spray glazing is used, with a glazing amount of 400-600g / m².
[0055] The glazing process primarily uses a bell-shaped glaze application method, supplemented by spray glazing for repairs, to ensure that the high-density glaze slurry of 1.75~1.85 g / cm³ forms a uniform, smooth, and consistent glaze layer on the brick surface. When the glaze application amount is less than 400g / m², the glaze layer is too thin, the absolute amount of activated alumina is insufficient, the anti-fouling layer cannot be completely covered, and the anti-fouling level remains at level 3. When the glaze application amount is greater than 600g / m², the glaze layer is too thick, making it difficult for gas to escape during firing, easily causing bubbles and glaze cracks, while also increasing costs.
[0056] During glazing, the main body is first glazed using a bell-shaped glazing applicator. The glaze flows out evenly from the overflow port of the bell-shaped applicator, forming an arc-shaped glaze curtain. The brick blank passes through the glaze curtain at a uniform speed of 15~25 m / min, so that the glaze is evenly covered on the surface of the brick blank. This process must ensure that the glaze curtain is continuous and stable. After the bell-shaped applicator glazes, the glaze coverage of the brick blank is checked by manual visual inspection or an automatic detection system. For the edges of the brick blank or areas with uneven glaze, an automatic glazing machine is used for spot repair or edge repair to ensure that the glaze layer coverage is 100% and the thickness is uniform. The glazing pressure is 0.2~0.4 MPa, the nozzle diameter is 0.8~1.2 mm, and the spray distance is 20~30 cm.
[0057] Preferably, the firing temperature is set with control points M21, M31, M45, M53 and M57, and the temperatures at each control point are as follows: brick surface temperature: M21: 918±10℃, M31: 1020±10℃, M45: 1105±10℃, M53: 1175±10℃, M57: 1190±1℃; brick bottom temperature: M021: 864±10℃, M027: 1030±10℃, M043: 1111±10℃, M055: 1180±10℃, M057: 1193±1℃. The heating time for each zone is as follows: 20-28 min for kiln entry → M21, 7-11 min for M21 → M31, 9-14 min for M31 → M45, 7-10 min for M45 → M53, and 3-6 min for M53 → M57. After passing through the M57 control point, maintain the temperature for 7-8 minutes; then cool to 850±10℃ for 3-5 minutes, then cool to 550±10℃ for 8-12 minutes, and finally allow to cool naturally.
[0058] The control of the heating and cooling curves during firing is mainly reflected in the following aspects: First, effectively eliminating thermal stress in the body and glaze fundamentally prevents the formation of macroscopic cracks. Quartz undergoes an α→β phase transformation with a volumetric abrupt change of approximately 0.8% around 573℃. Traditional rapid cooling easily leads to unreleased thermal stress between the body and glaze due to the difference in their coefficients of thermal expansion, resulting in penetrating macroscopic cracks (glaze cracks) on the glaze surface or hidden cracks in the body. This invention extends the slow cooling section to 8-12 minutes, providing sufficient time for the brick body to shrink uniformly within the critical quartz phase transformation zone. This allows thermal stress to gradually dissipate through a viscoelastic relaxation mechanism, significantly improving the structural integrity of the product.
[0059] Secondly, it enables the aluminate microcrystals generated by activated alumina to be fully stabilized and solidified, thus enhancing antifouling performance. The activated alumina (calcined bauxite powder) introduced into the process reacts with Ca in the high-temperature stage. 2+ Mg 2+ The calcium aluminate, magnesium aluminum spinel, and other nanocrystals generated during the reaction continue to undergo lattice ordering and composition homogenization during the slow cooling process. The slow cooling of 8-12 minutes effectively avoids lattice distortion or microcracks caused by thermal shock from excessive cooling, preventing them from becoming new channels for contamination. This provides sufficient time for the anti-fouling microcrystals to set, allowing them to form a dense and defect-free transition layer with the glaze glass phase.
[0060] Furthermore, it significantly promotes uniform annealing of the glass phase, greatly improving the chemical stability of the glaze. Since the glass phase in the glaze is in a thermodynamically metastable state at high temperatures, sufficient structural relaxation (annealing) is required to reduce internal stress and eliminate structural defects. By extending the slow cooling time to 8–12 minutes, broken bonds and defects caused by thermal vibrations in the glaze's glass network structure are rebonded and repaired, reducing the amount of non-bridging oxygen and enhancing the connectivity of the glass network. This annealing effect not only improves the glaze's resistance to acid and alkali corrosion but also reduces the chemical adsorption sites of stains on the glaze, bringing significant indirect benefits to its anti-fouling performance.
[0061] Finally, achieving a balanced cooling rate on the upper and lower surfaces of the brick blank effectively prevents product deformation. In roller kilns, the upper surface of the brick blank is directly exposed to the kiln airflow, resulting in a faster cooling rate, while the lower surface, in contact with the rollers, experiences a slower cooling rate. Traditionally, the shorter slow cooling time easily leads to warping and deformation of the brick blank (especially for large-format thin slabs) due to the large difference in cooling rates between the upper and lower surfaces. This invention extends the slow cooling section to 8-12 minutes, combined with independent adjustment of the cooling airflow above and below the rollers, to achieve a more balanced cooling rate on the upper and lower surfaces of the brick blank. This effectively eliminates warping caused by asymmetrical thermal shrinkage, significantly improving the flatness and yield of ceramic tiles.
[0062] In a specific embodiment, the cooling method is divided into three stages: The first stage is the rapid cooling stage. Immediately after leaving the insulation zone, the brick blank enters the rapid cooling stage, using air cooling. Room temperature air is sprayed at high speed onto the surface of the brick blank through symmetrically arranged rapid cooling ducts, rapidly cooling it from approximately 1190℃ to approximately 850℃ within 3-5 minutes. Rapid cooling quickly solidifies and sets the glaze, preventing excessive grain growth. Simultaneously, in cases involving fused dry granule technology, the difference in thermal expansion coefficients between the A-grade dry granules and the protective glaze generates shrinkage stress at this stage, forming microcrack initiation points.
[0063] The second stage is the slow cooling stage. After rapid cooling, the brick blank enters the slow cooling stage, where indirect air cooling or heat exchange cooling is used. By adjusting the cooling air volume or heat exchanger flow rate, the temperature is slowly cooled from approximately 850℃ to approximately 550℃ within 8-12 minutes. Strict control of the cooling rate is crucial in this stage. Quartz undergoes an α→β phase transformation near 573℃, accompanied by a significant volume change. Excessive cooling can easily lead to macroscopic cracks in the glaze and the brick body; therefore, slow cooling is essential to ensure sufficient release of thermal stress.
[0064] The third stage is the final cooling stage. After slow cooling, the brick blanks enter the final cooling stage at the kiln tail, where natural cooling is supplemented by low-volume forced convection, gradually reducing the temperature from approximately 550℃ to below 80℃ before exiting the kiln. No special control is required at this stage, and the exit temperature is <80℃.
[0065] A ceramic tile prepared by the above-mentioned preparation method, having a glaze anti-fouling level ≥4 and a glaze gloss ≥94°.
[0066] The main equipment of this scheme is a natural gas open-flame wide-body roller kiln. A roller kiln is a continuous industrial kiln that uses rotating rollers to transport materials, sequentially completing processes such as preheating, sintering, and cooling. It is widely used in the firing of ceramic wall and floor tiles and daily-use ceramics. Currently, roller kilns commonly employ PID intelligent temperature control technology, with temperature differences ≤ ±1℃ and cross-sectional temperature differences ≤ ±5℃, providing a foundation for precise temperature control. The transmission method is as follows: the brick blanks are placed on ceramic rollers, which are driven to rotate by a motor, allowing the brick blanks to pass through each section of the kiln at a uniform speed.
[0067] This solution utilizes a distributed intelligent temperature control system. In roller kiln temperature control, traditional PID control is ineffective due to the difficulty in establishing an accurate mathematical model of the controlled object. This solution employs a relay feedback-based PID parameter self-tuning method to determine initial PID parameters. Then, using fuzzy control theory, the PID parameters are corrected in real-time based on the absolute value of the deviation and the cumulative absolute value of the deviation during system operation. When parameters or operating conditions change, the PID parameter values are gradually adjusted to ensure the system control performance remains optimal, achieving online intelligent correction of the PID parameters.
[0068] This intelligent control system uses RS-485 serial communication to form a distributed intelligent control system for centralized monitoring of the roller kiln temperature. It has been running continuously in the field for a long time with stable performance, high reliability, and good control performance.
[0069] In addition, to further overcome the large time delay characteristics of the roller kiln system, an adaptive PID control method based on deep reinforcement learning can also be adopted. The PID controller parameters are adaptively adjusted through the TD3 algorithm, and the Smith predictor is used to eliminate the influence of the time delay of the roller kiln system, so that the root mean square error of temperature control is reduced by 5.58~11.42 compared with traditional PID control.
[0070] This solution replaces the outdated relay control system with a PLC and a high-precision temperature control module, integrating over 100 temperature acquisition points. It dynamically adjusts the heating power using a PID self-tuning algorithm to avoid temperature overshoot or lag. By introducing a temperature curve prediction function, it can anticipate temperature fluctuation trends based on historical production data and product firing processes, automatically compensating for heating parameters and improving temperature stability by 40%.
[0071] The specifications of the conventional raw materials used in Examples 1-4 and Comparative Examples 1-5 are shown in Table 1 below: Table 1 Raw Material Specifications
[0072] The mineral raw material formulations for Examples 1-4 are as follows (by weight): 30 parts potassium feldspar, 15 parts sodium feldspar, 20 parts quartz powder, 10 parts calcite, 2 parts dolomite, 2 parts calcined talc, 2 parts zinc oxide, 1 part barium carbonate, 3 parts zircon sand powder, and calcined bauxite powder in the weight proportions shown in Table 2 below. The anti-fouling grade of the glaze was tested according to GB / T3810.14-2016 standard, and the gloss of the glaze was tested according to GB / T13891-2008 standard.
[0073] Table 2 Process parameters and properties of fired ceramic tiles in Examples 1-3
[0074] The preparation methods of Comparative Examples 1-5 are the same as those in Example 2, with the differences shown in Table 3 below: Table 3. Process parameters and properties of fired ceramic tiles in Comparative Examples 1-5
[0075] In summary, only under the specified range of active aluminum source addition and precise firing regime stipulated in this scheme can a product with antifouling level 5 and gloss ≥95° be obtained. Comparative Example 1 showed the worst antifouling performance; without active alumina, a dense transition layer could not be formed, resulting in numerous open pores on the glaze surface and significant ink penetration, proving that active alumina is a necessary component. In Comparative Example 2, traditional α-Al₂O₃ had low reactivity and served only as an inert filler, failing to effectively seal pores, demonstrating that not all alumina is effective; only active alumina or calcined bauxite powder with equivalent activity is effective. In Comparative Example 3, insufficient active alumina was used, failing to form a continuous antifouling layer, with localized penetration, indicating that insufficient dosage could not achieve the target antifouling level. In Comparative Example 4, excessively high temperatures resulted in a violent reaction and excessive bubble production; in Comparative Example 5, low temperatures led to insufficient firing. Both excessively high and low temperatures resulted in poor antifouling performance.
[0076] The protective glaze prepared using the formula and process of this invention improves the anti-fouling level from level 3 to level 4 or above, while the glaze surface gloss is ≥94° and has good transparency.
[0077] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0078] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing ceramic tiles with improved glaze stain resistance, characterized in that, The protective glaze layer is fired from a protective glaze material, the raw materials of which include: potassium feldspar, sodium feldspar, quartz powder, calcite, dolomite, calcined talc, zinc oxide, barium carbonate, zircon sand powder, and materials containing active alumina; wherein, the active alumina is alumina with γ-Al2O3, δ-Al2O3, or θ-Al2O3 as the main crystalline phase, and the content of active alumina is 1.8~2.5% (mass ratio) of the glaze raw materials; The firing time for the protective glaze is 46-69 minutes, with the highest surface temperature of the fired brick blank being 1190±1℃ and the holding time at the highest temperature being 7.5±0.5 minutes.
2. The method for preparing ceramic tiles with improved glaze stain resistance according to claim 1, characterized in that: The material containing active alumina is calcined bauxite powder that has been calcined at 650~850℃.
3. The method for preparing ceramic tiles with improved glaze stain resistance according to claim 2, characterized in that, According to parts by weight, the raw materials for the glaze include: Potassium feldspar 28-35 parts, 12-18 parts of albite, 15-22 parts quartz powder 8-12 parts of calcite 1-3 parts dolomite 1-3 parts of calcined talc. 1-3 parts zinc oxide Barium carbonate 0.5-1.5 parts, 2-5 parts zircon sand powder 10-14 parts of calcined bauxite powder.
4. The method for preparing ceramic tiles with improved glaze stain resistance according to claim 1, characterized in that: The glaze is prepared by wet ball milling. The raw materials of the glaze, water and dispersant are added to the ball mill and ground and mixed. The glaze is milled until the fineness D90≤10μm and the specific gravity of the glaze slurry is 1.75-1.85g / cm³, and the glaze slurry is obtained.
5. The method for preparing a ceramic tile with improved glaze stain resistance according to claim 4, characterized in that: The glazing process employs a combination of bell-shaped glazing and spray glazing, with a glaze application rate of 400-600g / m².
6. The method for preparing ceramic tiles with improved glaze stain resistance according to claim 1, characterized in that: The firing temperature is controlled by points M21, M31, M45, M53, and M57. The temperatures at each control point are as follows: brick surface temperature: M21: 918±10℃, M31: 1020±10℃, M45: 1105±10℃, M53: 1175±10℃, M57: 1190±1℃; brick bottom temperature: M021: 864±10℃, M027: 1030±10℃, M043: 1111±10℃, M055: 1180±10℃, M057: 1193±1℃. The heating time for each zone is as follows: 20-28 min for kiln entry → M21, 7-11 min for M21 → M31, 9-14 min for M31 → M45, 7-10 min for M45 → M53, and 3-6 min for M53 → M57. After passing through the M57 control point, maintain the temperature for 7-8 minutes; then cool to 850±10℃ for 3-5 minutes, then cool to 550±10℃ for 8-12 minutes, and finally allow to cool naturally.
7. A ceramic tile, characterized in that: Prepared by the preparation method according to any one of claims 1-6, the glaze has a stain resistance level ≥ 4 and a gloss level ≥ 94°.